Changing treatment patterns in elderly patients with resectable colon cancer. Issue 3 (21st December 2012) - Kim, Gun Min; Ahn, Joong Bae; Rha, Sun Young; Kim, Han Sang; Kang, Beodeul; Kim, Min Whan; Choi, Soo Yeon; Roh, Jae Kyung; Chung, Hyun Cheol; Kim, Nam Kyu; Shin, Sang Joon
Abstract Aim To evaluate changing treatment patterns and survival outcomes of elderly patients (age 70 years or older) with resectable colon cancer over the past 15 years. Methods A total of 857 patients aged over 70 years who were managed for a resectable colon cancer between 1994 and 2010 were identified and their clinical variables were analyzed retrospectively. Results The patients' median age was 74 years (range: 70–94 years). In all, 171 patients (20%) were stage I, 375 (43.8%) were stage II and 311 (36.3%) were stage III. Over 95% of all patients underwent surgery regardless of age or diagnosis year. In stage III colon cancer the proportion of patients who received adjuvant treatment increased the more recent the year of diagnosis (1994–2000, 47%; 2001–2005, 66%; 2006–2010, 70%; P = 0.017). According to analysis by age group, older patients were less likely to receive adjuvant chemotherapy in both stage II (more than 75 years, 47.3%; 70–74 years, 59.4%; P < 0.001) and stage III (more than 75 years, 51.1%; 70–74 years, 76.7%; P < 0.001). Age‐adjusted Charlson comorbidity index (CCI) is an independent prognostic factor for overall survival in stage II colon cancer patients. Conclusion Elderly patients with resectable colon cancer received surgical treatment in more than 95% of cases without reference to age or diagnosis year. The proportion of patients who received adjuvant treatment increased according to the recency of diagnosis, but decreased abruptly according to increase in age.